G6PD deficiency as a underrecognized genetic risk factor for rare neurological disorders: evidence from a population-based genetic analysis - Peng, Qi; Li, Siping; Lv, Fen; Zeng, Xiaomei; Cheng, Qingqiu; Zhong, Baimao; Lu, Xiaomei (Frontiers in Genetics, 2026)
BackgroundGlucose-6-phosphate dehydrogenase (G6PD) deficiency is traditionally recognized as a risk factor for drug- or infection-induced hemolytic anemia. Emerging evidence implicates potential roles of G6PD in neurodevelopment, yet its association with rare neurological disorders remains underexplored in population-based genetic studies, especially within the Chinese population.MethodsWe conducted a retrospective case-control study utilizing whole-exome sequencing (WES) data from a Chinese cohort. Six most prevalent pathogenic G6PD variants in China were screended in children with rare neurological disorders (n = 211) and in controls without neurological involvement (n = 202). Genotype and carrier frequency comparisons were performed. Stratified analyses were performed based on diagnostic certainty and the presence of de novo mutations. Multivariable logistic regression was employed to calculate sex-adjusted odds ratios (ORs) to control for potential sex-related confounding.ResultsAfter adjusting for sex, the overall carrier rate of pathogenic G6PD variants was significantly higher in patients with neurological disorders than in controls (adjusted OR = 2.44, 95% CI: 1.18–5.06, p = 0.014). Further comparisons across specific groups revealed distinct patterns: affected male patients had a higher carrier rate than their own unaffected fathers (OR = 2.30, 95% CI: 1.08–4.91, p = 0.043), and mothers of case patients showed a higher carrier rate than mothers of controls (OR = 2.03, 95% CI: 1.09–3.78, p = 0.030). The variants NM_001042351.3: c.1376G>T (G6PD Canton) and NM_001042351.3:c.1388G>A (G6PD Kaiping) were the most prevalent across all groups.ConclusionThis population-based genetic analysis provides preliminary evidence that G6PD deficiency may be a underrecognized genetic risk factor for rare neurological disorders in Chinese children. The findings suggest a potential maternal genetic contribution and indicate that the phenotypic spectrum of G6PD deficiency may extend beyond hematological manifestations to include neurodevelopmental vulnerability. Important limitations include the lack of functional validation and the use of a clinical control group. Further prospective studies incorporating G6PD enzyme activity assessment and functional investigations are warranted to elucidate the underlying mechanisms.